Participative leadership style on organizational commitment with organizational culture as a moderating - Faizal Arief; Sulastri Sulastri (Human Resource Management Studies, 2021)
This research analized: (1) the influence of Partisipative Leadership Style on Organizational Commitment at PDAM Tirta Langkisau (2) the influence of Partisipative Leadership Style on Organizational Commitment through Organizational Culture at PDAM Tirta Langkisau. The study is causal research. The population were employees of PDAM Tirta Langkisau, totaling 103 people. The number of sample determined using Slovin collected samples obtained by 82 people taken using proportional cluster random sampling. Collecting data using a questionnaire with Likert scale. The analysis technique used is SEM SmartPLS analysis. This research found that: (1) Partisipative Leadership Style has positive and significant effect on organizational commitment in PDAM Tirta Langkisau, (2) organizational culture has significantly moderate the relationship between partisipative leadership style on organizational commitment in PDAM Tirta Langkisau.